Resilience-Based Sustainability Indicators for Freshwater Lakes with Application for Dongting Lake, China - Xu, Li; Marinova, Dora; Xin, P.; Guo, Xiumei (Canadian Center of Science and Education, 2015)
This paper develops a framework for incorporating resilience into sustainability indicators for freshwater lakes. The sustainability of freshwater lakes is important from both, an ecological point of view and within a socio-economic context, as these systems are sensitive to external disturbances and susceptible to changes in land coverage, vegetation distribution, hydrological conditions and perturbations from human activities. Existing sustainability indicators do not incorporate resilience and consequently do not reflect the ability of the lake to withstand the impacts of shocks and improve its current state for achieving sustainable over time. The developed resilience framework is applied for the case of China’s Dongting Lake, which is exposed to the impacts of the Three-Gorges Dam in addition to experiencing ecological and socio-economic changes. The resilience perspective allows 37 indicators to be developed to describe and monitor the Lake’s sustainability based on considering known, possible and unknown future changes. They can inform any future resilience management of its complex ecological system.